“It's Such a Taboo Subject, Everybody's Scared to Talk About It”: Fijian Sportswomen's Experiences of Menstruation - Gibbons, Agatha Elizabeth; Thorpe, Holly; Hemi, Keakaokawai Varner; Pedlar, Charles; Bruinvels, Georgie; Hamilton, Bruce (Journal of sport and social issues, 2024)
Despite a growing body of research focused on women's experiences of menstruation in sports, most of this has been done by white women on white women and then applied to sportswomen from diverse cultural and ethnic backgrounds. Very rarely are the menstruation-related experiences of Black, Indigenous, and women of color considered, let alone the focus of such studies. To date, no research has explored Pacific sports women's experiences of menstruation. In this research, we adopt a contextually relevant Masi methodology approach to understand how Pacific sports women navigate different knowledge (i.e., scientific, family, cultural, religious, and social media sources) about menstruation in their everyday lives. Drawing upon Talanoa sessions (informal interviews and focus groups) with 21 Fijian sportswomen from a range of sports, we highlight the many ways sportswomen's knowledge has been overlooked, and their health needs ignored. We reveal how cultural and family knowledge shapes Fijian sportswomen's menstrual practices in and out of sports, and the lingering silences and stigma shaping coaching and medical support. Thus, this research seeks to improve the support structures for Pacific sportswomen by expanding sports and health providers’ understandings of culturally specific menstrual health needs and knowledge.